Mapping the Future of Indonesian Sports: A Systematic Review of Policy Analysis and Implementation - Reza Aziz Prasetya, Muhammad; Firmansyah, Awang; Wahyudi, Heri; Putra Bimantoro, Aprilyan; Hsueh wen Chow (Proceeding of International Joint Conference on UNESA, 2025)
Sport holds a strategic role in Indonesia’s national development, contributing to public health, community empowerment, and the cultivation of high-performing athletes. In response, the government has introduced various sports policies to enhance public participation and improve the overall quality of sports development. However, despite these efforts, the implementation of sports policies still encounters numerous challenges, including limited financial support, suboptimal management of sports facilities, and weak coordination among stakeholders. This study aims to systematically analyze the development and implementation of sports policies in Indonesia and identify the major obstacles and potential improvements. Using the PRISMA method, a systematic review was conducted based on literature from databases such as Garuda, Google Scholar, and EBSCOhost, covering the period from 2017 to 2025. Ten qualitative studies that met the inclusion criteria were analyzed. The review found that while certain policies have positively influenced public engagement in sports, critical issues remain unresolved. The findings highlight the need for better budgeting, improved infrastructure management, enhanced collaboration between government agencies and sports organizations, and stronger community support. Recommendations include increasing investment in sports, improving facility accessibility and quality, and strengthening inter-agency coordination to achieve sustainable sports development. This review provides evidence-based insights to inform future policy formulation and supports the broader objective of advancing Indonesia’s sports ecosystem.